Makna Gerak Tari Piriang Suluah Di Sanggar Aguang Kelurahan Sigando Kecamatan Padangpanjang Timur Kota Padangpanjang - Khairunnisa Khairunnisa; Darmawati Darmawati (FBS Universitas Negeri Padang, 2022)
This study aims to determine and describe the meaning of the movement of the Piriang Suluah Dance in Sigando Village, East Padangpanjang District, Padangpanjang City. The type of research used is qualitative with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as writing instruments and cameras. This type of data uses primary data and secondary data. Data collection techniques were carried out employing library research, observation, interviews and documentation. The steps to analyze the data are data collection, data reduction and data presentation. The results showed that the overall performance of the Piriang Suluah dance moves meant hard work, responsibility and high social values. The Piriang Suluah dance movement is a reflection of the Sigando community whose life is farming and playing. Such as the movements of maniti pamatang, ramo-ramo tabang, maalau buruang, mangisai straw, tapuok rangik. Suluah which is placed above the head means a street light because in ancient times there was no electricity as it is today. Every performance that is performed at a different time and place will experience a change in the arrangement of movements or floor patterns. However, in the Piriang Suluah Dance performances, it is more dominant to use a circular floor pattern. The number of dancers in the Piriang Suluah Dance is independent and the age of the dancers is not limited. The existence of the Piriang Suluah Dance in the community is still preserved by the local community. This is evidenced that the Piriang Suluah Dance is still used in big events in Padangpanjang.